Influence of Hole Arrangement on the Section of Cavity Formed by Cutting Blast - Xianglong Li; Qiang Li; Jianguo Wang; Zichen Wang; Hao Wang; Zihao Tao (Geofluids)
In order to optimize the arrangement of cutting holes in tunnel blast in Dahongshan Copper Mine, theoretical analysis and numerical simulation were combined to preliminarily determine the diameter of the hollow hole and the distance between the charge hole and the hollow hole during cut blast, which was verified through the field blast test. The research results show that with the increase of the hole diameter, the peak compressive stress of rock surrounding the empty hole gradually decreases, and the peak tensile stress gradually increases, which is consistent with the calculation results; when the hole diameter is 10 cm, the two first blast holes are arranged horizontally and 30 cm from the empty hole, two second blast holes are arranged vertically and 40 cm away from the empty hole, and the four third blast holes are arranged at a horizontal distance of 45 cm and a vertical distance of 45 cm from the empty hole; the contour area in numerical simulation is the maximum. The difference in contour area, contour width, and contour and contour height between the measured value and the simulation result is 5.3%, 3.3%, and 3.4%, respectively, indicating that the combination of theoretical calculation and numerical simulation is suitable for prediction of cavity section after blast in tunnel excavation.